2014
DOI: 10.1111/cobi.12376
|View full text |Cite
|
Sign up to set email alerts
|

Identifying impediments to long‐distance mammal migrations

Abstract: In much of the world, the persistence of long-distance migrations by mammals is threatened by development. Even where human population density is relatively low, there are roads, fencing, and energy development that present barriers to animal movement. If we are to conserve species that rely on long-distance migration, then it is critical that we identify existing migration impediments. To delineate stopover sites associated with anthropogenic development, we applied Brownian bridge movement models to high-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 38 publications
2
103
2
2
Order By: Relevance
“…The ability or frequency at which individuals cross roads will likely remain a priority in the field of road ecology, as a road can reduce landscape permeability by acting as a barrier or filter to movement and, therefore, has the potential to influence population persistence. One study highlighted that the barrier effects of roads are a particular concern for species that migrate, such as the pronghorn (Antilocapra Americana) [46]. Of the studies included in this review, nine identified the characteristics of road that influenced permeability, such as traffic volume [46][47][48], road width or the number of lanes [47,49], and road surface type.…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
“…The ability or frequency at which individuals cross roads will likely remain a priority in the field of road ecology, as a road can reduce landscape permeability by acting as a barrier or filter to movement and, therefore, has the potential to influence population persistence. One study highlighted that the barrier effects of roads are a particular concern for species that migrate, such as the pronghorn (Antilocapra Americana) [46]. Of the studies included in this review, nine identified the characteristics of road that influenced permeability, such as traffic volume [46][47][48], road width or the number of lanes [47,49], and road surface type.…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
“…These disturbances include natural gas and oil extraction, open-pit mining, residential developments, restrictive fencing, and recreational development and use (Sawyer et al 2006, Sawyer et al 2009a, Lendrum et al 2012, Lendrum et al 2013, Sawyer et al 2013, Seidler et al 2014. These developments often result in direct or indirect loss of wildlife and habitat, which also influences behavior and habitat use of affected species, and can lead to changes in survival and recruitment (Cole et al 1997, Sawyer et al 2006, Bolger et al 2008, Sawyer et al 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists have attempted to quantify the impacts of human disturbances across a variety of migratory ungulates (Lendrum et al 2012, Lendrum et al 2013, Sawyer et al 2013, Seidler et al 2014). Natural gas exploration has been the primary focus of that research because of the recent expansion of exploration across the western United States (Sawyer et al 2006, Sawyer et al 2009a, Beckmann et al 2012, Lendrum et al 2012, Lendrum et al 2013, Sawyer et al 2013, Buchanan et al 2014, Seidler et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations